Analisis Pengawasan Cukai Hasil Tembakau Di Kantor Pengawasan Dan Pelayanan Bea Dan Cukai Tipe Madya Pabean A Jakarta Tahun 2020-2022 - Kuntoro, Triandi; Rahmi, Notika (Jurnal Ilmu Administrasi Publik, 2024)
The phenomenon of non-tax state revenue (PNBP) from the tobacco sector that has not been optimized makes the Ministry of Finance, Directorate General of Customs and Excise must try to find new solutions and breakthroughs to increase state revenue. Until now, the government continues to optimize the sector. According to Indonesia Law no. 39 of 2007 concerning Amendments to Law no. 11 of 1995 concerning Excise, based on article 1 excise is defined as "State levies imposed on certain goods that have the properties or characteristics stipulated in this law". This study aims to analyze how the level of tobacco excise supervision at KPPBC TMP A Jakarta, what are the inhibiting entities faced by KPPBC TMP A and what are the driving entities that support KPPBC TMP A Jakarta in supervising tobacco excise to maintain smooth state revenue. The research method used is qualitative with descriptive research type. Data sources consist of primary data in the form of interviews and secondary data in the form of documentation data. The results of this study indicate: Supervision of tobacco excise has been maximized but there are several things that need to be improved, among others, namely the number of employees, employee knowledge and compliance with government regulations. It is expected that the supervision of tobacco excise in order to increase PNBP will run optimally.